1997
DOI: 10.1007/bf02397233
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundaries contribution to the complex susceptibility of KCu-Doped YBCO high-temperature superconductors

Abstract: We present results concerning the e[. [L'ct o/'adding potassium and excess copper (1 +5wt.%) complex susceptibility Z,,~ = Z'-JZ" ~[" K('u-doped YBCO was measured as a function of the temperature, the magnetic field amplitude and the KCu concentration. The behavior of the intergraln loss temperature T m was analyzed through the relationship h ~ a(1 -O".The results obtained showed that the presence o/" K3UuO 2 on the gram boundaries changes drastically the intergranular coupling and. within certain concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…A second peak, which we associate with intergrain losses, is clearly seen in the case of KCu:YBCO; such a peak was not observed in the case of YBCO (CuO) and Rb:YBCO. Our previous investigations [8] confirmed that the irreversibility line in the (H, T ) plane for the intergranular peak obeyed the h ac = a(1 − t) n law, with different crossovers versus the applied field for YBCO and KCu:YBCO. Figure 3 also shows typical YBCO and KCu:YBCO microstructures, as observed by SEM.…”
Section: Effect Of the Additive Phases On The Grain Boundaries On The...supporting
confidence: 63%
“…A second peak, which we associate with intergrain losses, is clearly seen in the case of KCu:YBCO; such a peak was not observed in the case of YBCO (CuO) and Rb:YBCO. Our previous investigations [8] confirmed that the irreversibility line in the (H, T ) plane for the intergranular peak obeyed the h ac = a(1 − t) n law, with different crossovers versus the applied field for YBCO and KCu:YBCO. Figure 3 also shows typical YBCO and KCu:YBCO microstructures, as observed by SEM.…”
Section: Effect Of the Additive Phases On The Grain Boundaries On The...supporting
confidence: 63%
“…Meanwhile, the value of Tcj decreased from 87.8 K for 0.0 mol% to 85.5 K for 7.0 mol% BZO addition (2.3 K). The decrease of Tcj with the increasing of BZO addition for both COP and SS samples indicates weakening of intergranular coupling perhaps due to the increasing of impurities at the grain boundaries [35,36]. However, the larger decrease of Tcj in the SS samples implies more severe degradation of grain coupling caused by BZO addition compared to the COP samples.…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 93%